Space in the tropics : from convicts to rockets in French Guiana - Redfield, Peter, 1965- (University of California Press, 2000)
Rockets roar into space--bearing roughly half the world's commercial satellites--from the same South American coastal rainforest where convicts once did time on infamous Devil's Island. What makes Space in the Tropics enthralling is anthropologist Peter Redfield's ability to draw from these two disparate European projects in French Guiana a gleaming web of ideas about the intersections of nature and culture.